PENERAPAN MODEL APTITUDE TREATMENT INTERACTION UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR MATEMATIKA SISWA SMPN 3 PRAYA TIMUR TAHUN PELAJARAN 2016/2017 - Aminah, Siti; Sanapiah, sanapiah; Febrilia, Baiq Rika Ayu (Universitas Pendidikan Mandalika (UNDIKMA), 2017)
Lack of student interest in learning mathematics and the use of methods which are not effective in the learning process leads to lower student learning outcomes. One alternative solution to overcome this problem is to apply the learning model ATI. This study aimed to describe the Model ATI to Increase Interests and Student learning outcomes on the Topic Circle at SMPN 3 Praya Timur in academic year 2016/2017. This research is a classroom action research. This study consisted of two cycles. Each cycle consists of four stages: plan, execution, observation, and reflection. The data sources obtained from class VIII-A, amounting to 29 people. Types of data obtained are quantitative and qualitative data. The results showed an increase in student learning outcomes with a percentage of 42% to 86%. While the student's interest in learning increased from 1.75 to 1.85. The results showed that the use of ATI Learning Model can Increase the Interest and Results of Academic Students of SMPN 3 Praya Timur in the academic year 2016/2017.